Tolerance Value in Kampung Pulo, Garut District (Ethnopedagogical Study) - Mulyadi, Adad (International Conference on Elementary Education, 2021)
The background of this research is the large diversity of religious traditions in Pulo village that have a tolerance value. This study aims to provide an overview of the value of tolerance in Pulo Village and Ethnopedagogical in Pulo Village. The method used in this research is the descriptive method. In Pulo Village, some traditions are maintained, including not being violated, such as not building more than seven buildings, not beating gongs, and being prohibited from raising four-legged animals. The value of tolerance in Pulo village is very high because in its history Ki Dalem Arif spread the religion of Islam without disturbing the beliefs that had been previously practiced in the village. Until now, religious tolerance is very well maintained, when Muslims celebrate big days and when Hindus celebrate their religious holidays, everything is side by side and mingles. In addition to the value of tolerance, this study also explores the ethnopedagogical value in Pulo village which includes Human Morals towards God, Human Morals in Person, Human Morals on other Humans, Human Morals to Nature, Human Morals at Time, and Human Morals in achieving Welfare of Birth and Mind.